The truth about Lion. IN Features. - Berenstain, Adam.; Bohon, Cory.; Bookwalter, J.R.; Ochs, Susie; Vargus, Nic.
Whether you're an early adopter, or a "wait till version 10.7.1" type we'll show you how to get your paws on the best of Mac OS 10.7 Lion.
Keywords: Mac OS; iOS (Electronic resource); Mac OS 10.7 Lion; 0.6 boot drive; Mac OS X Cougar